Evaluación del sistema de tratamiento de aguas residuales en la disminución de la demanda química de oxígeno, en industrias del Shanusi, Yurimaguas - Pinchi Cardenas, Diomedes Javier (2013)
The water used in the various human activities undergoes modifications in their physical, chemical and biological properties. Por this reason, the water coming from the different processes and activities domestic, industrial and agricultura!, etc. , are called wastewater and íts discharge ínto bodies of water can be harmful to the people, for the same bodies of water and for the various forms of Iife. Thus, it is important to remove pollutants from wastewater before them to be reused or discharged into bodies of water, surface water, groundwater and coastal. The removal of pollutants is carried out according to levels that must respond, according to specific rules of each country and to the uses of the water bodies. The present work, it has as aím, determine the efficiency of the Treatment of residual Waters in the System ofTreatment ofResidual Waters in Industries ofthe Shanusi S.A There were 8 sampling of the influent and effluent sampling 8 during the rain season and another in dry season, for microbiological analysis and physicochemical analysis. Ultimately there was gathered a whole of 24 samples. The analysis of the DQO was realized using the equipment Thermo Spectronic Genesys 20. The results were analyzed using EXCEL by means of the t - paired for two variables and bar graphs. They reveal that there exists significant difference between the water of the tributary and effluent in the treatment plant during two analyzed epochs; the results are below Project of Law - Maximum Permissible Limits for Effluent of Activities of the Sector Industry to Bodies Recipients, obtained after the process of sedimentation in the plant of treatment, on having analyzed the tributary and effiuent both in epoch of rain and in dry epoch. Therefore, the plant meets with an efficient operation, so that the water should be reused for consumption and irrigation. Key words: remove pollutants, treatment plant.